Improved Bounds for Acyclic Job Shop Scheduling - Feige, Uriel; Scheideler, Christian (Combinatorica)

Improved bounds for the unsplittable flow problem - Kolman, Petr; Scheideler, Christian (SODA)

Compact, adaptive placement schemes for non-uniform requirements - Brinkmann, André; Salzwedel, Kay; Scheideler, Christian (SPAA)

Algorithms for fault-tolerant routing in circuit switched networks - Bagchi, Amitabha; Chaudhary, Amitabh; Scheideler, Christian; Kolman, Petr (SPAA)

Models and Techniques for Communication in Dynamic Networks - Scheideler, Christian (STACS)

Storage Management as Means to cope with Exponential Information Growth - Scheideler, Christian; Salzwedel, Kay; Meyer auf der Heide, Friedhelm; Brinkmann, André; Vodisek, Mario; Rückert, Ulrich (Proceedings of SSGRR 2003)
The advances in Internet technology have led to tremendous improvements in business, education, and science and have changed the way we think, live, and communicate. Information exchange has become ubiquitous by the possibilities offered through modern technologies. We are able to offer information 24 hours a day through our web sites and can leave messages every time and from anywhere in the world. This change in communication has led to new challenges. Enterprises have to deal with an information amount that doubles every year. The technological foundation to cope with this information explosion is given by Storage Area Networks (SANs), which are able to connect a great number of storage systems over a fast interconnection network. However, to be able to use the benefits of a SAN, an easy-to-use and efficient management support has to be given to the storage administrator. In this paper, we will suggest new storage management concepts and we will introduce a new management environment that is able to significantly reduce management costs and increases the performance and resource utilization of the given SAN infrastructure.

Smoothed Motion Complexity - Damerow, Valentina; Meyer auf der Heide, Friedhelm; Räcke, Harald; Scheideler, Christian; Sohler, Christian (ESA)

Anycasting in Adversarial Systems: Routing and Admission Control - Awerbuch, Baruch; Brinkmann, André; Scheideler, Christian (ICALP)

Peer-to-peer systems for prefix search - Awerbuch, Baruch; Scheideler, Christian (PODC)

Perfectly Balanced Allocation - Czumaj, Artur; Riley, Chris; Scheideler, Christian (RANDOM-APPROX)

On local algorithms for topology control and routing in ad hoc networks - Jia, Lujun; Rajaraman, Rajmohan; Scheideler, Christian (SPAA)

Information gathering in adversarial systems: lines and cycles - Kothapalli, Kishore; Scheideler, Christian (SPAA)

Simple On-Line Algorithms for the Maximum Disjoint Paths Problem - Kolman, Petr; Scheideler, Christian (Algorithmica)

Group Spreading: A Protocol for Provably Secure Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (ICALP)

A Distributed Hash Table for Computational Grids - Riley, Chris; Scheideler, Christian (IPDPS)

Robust Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (IPTPS)

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IWIA)

The hyperring: a low-congestion deterministic data structure for distributed environments - Awerbuch, Baruch; Scheideler, Christian (SODA)

Consistent and compact data management in distributed storage systems - Awerbuch, Baruch; Scheideler, Christian (SPAA)

Pagoda: a dynamic overlay network for routing, data management, and multicasting - Bhargava, Ankur; Kothapalli, Kishore; Riley, Chris; Scheideler, Christian; Thober, Mark (SPAA)

The effect of faults on network expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (SPAA)

Transparent Data Structures, or How to Make Search Trees Robust in a Distributed Environment - Korzeniowski, Miroslaw; Scheideler, Christian (ISPAN)

Supervised Peer-to-Peer Systems - Kothapalli, Kishore; Scheideler, Christian (ISPAN)

Efficient Broadcasting and Gathering in Wireless Ad-Hoc Networks - Onus, Melih; W. Richa, Andrea; Kothapalli, Kishore; Scheideler, Christian (ISPAN)

Constant density spanners for wireless ad-hoc networks - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; W. Richa, Andrea (SPAA)

How to spread adversarial nodes?: rotate! - Scheideler, Christian (STOC)

Overlay networks for wireless ad hoc networks - Scheideler, Christian (IMA Workshop on Wireless Communications)

Improved bounds for the unsplittable flow problem - Kolman, Petr; Scheideler, Christian (J. Algorithms)

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IEEE Trans. Mob. Comput.)

Distributed coloring in O/spl tilde/(/spl radic/(log n)) bit rounds - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; Schindelhauer, Christian (IPDPS)

Robust Random Number Generation for Peer-to-Peer Systems - Awerbuch, Baruch; Scheideler, Christian (OPODIS)

Towards a scalable and robust DHT - Awerbuch, Baruch; Scheideler, Christian (SPAA)

The Effect of Faults on Network Expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (Theory Comput. Syst.)

Towards a paradigm for robust distributed algorithms and data structures - Scheideler, Christian (6th International HNI Symposium on New Trends in Parallel and Distributed Computing)

Algorithms for Fault-Tolerant Routing in Circuit-Switched Networks - Bagchi, Amitabha; Chaudhary, Amitabh; Scheideler, Christian; Kolman, Petr (SIAM J. Discrete Math.)

Linearization: Locally Self-Stabilizing Sorting in Graphs - Onus, Melih; W. Richa, Andrea; Scheideler, Christian (Proceedings of the Nine Workshop on Algorithm Engineering and Experiments, ALENEX 2007, New Orleans, Louisiana, USA, January 6, 2007)

Towards Scalable and Robust Overlay Networks - Awerbuch, Baruch; Scheideler, Christian (6th International workshop on Peer-To-Peer Systems, IPTPS 2007, Bellevue, WA, USA, February 26-27, 2007)

A denial-of-service resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Proceedings of the Twenty-Sixth Annual ACM Symposium on Principles of Distributed Computing, PODC 2007, Portland, Oregon, USA, August 12-15, 2007)

A Denial-of-Service Resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Distributed Computing, 21st International Symposium, DISC 2007, Lemesos, Cyprus, September 24-26, 2007, Proceedings)

Distributed Computing in Sensor Systems, Third IEEE International Conference, DCOSS 2007, Santa Fe, NM, USA, June 18-20, 2007, Proceedings

SPAA 2007: Proceedings of the 19th Annual ACM Symposium on Parallelism in Algorithms and Architectures, San Diego, California, USA, June 9-11, 2007

Overlay Networks for Peer-to-Peer Networks - W. Richa, Andrea; Scheideler, Christian (Handbook of Approximation Algorithms and Metaheuristics.)

Dynamic and redundant data placement - Brinkmann, André; Effert, Sascha; Meyer auf der Heide, Friedhelm; Scheideler, Christian (IEEE International Conference on Distributed Computing Systems (ICDCS))
We present a randomized block-level storage virtualization for arbitrary heterogeneous storage systems that can distribute data in a fair and redundant way and can adapt this distribution in an efficient way as storage devices enter or leave the system. More precisely, our virtualization strategies can distribute a set of data blocks among a set of storage devices of arbitrary non-uniform capacities so that a storage device representing x% of the capacity in the system will get x% of the data (as long as this is in principle possible) and the different copies of each data block are stored so that no two copies of a data block are located in the same device. Achieving these two properties is not easy, and no virtualization strategy has been presented so far that has been formally shown to satisfy fairness and redundancy while being time- and space-eflcient and allowing an efficient adaptation to a changing set of devices.

Can ISPs and P2P users cooperate for improved performance? - Aggarwal, Vinay; Feldmann, Anja; Scheideler, Christian (ACM Computer Commucation Review)

Algorithms for Overlay Networks - Scheideler, Christian (Bulletin of the EATCS)

A jamming-resistant MAC protocol for single-hop wireless networks - Awerbuch, Baruch; W. Richa, Andréa; Scheideler, Christian (Proceedings of the Twenty-Seventh Annual ACM Symposium on Principles of Distributed Computing, PODC 2008, Toronto, Canada, August 18-21, 2008)

SPREAD: an adaptive scheme for redundant and fair storage in dynamic heterogeneous storage systems - Mense, Mario; Scheideler, Christian (Proceedings of the Nineteenth Annual ACM-SIAM Symposium on Discrete Algorithms, SODA 2008, San Francisco, California, USA, January 20-22, 2008)

Tiara: A Self-stabilizing Deterministic Skip List - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Stabilization, Safety, and Security of Distributed Systems, 10th International Symposium, SSS 2008, Detroit, MI, USA, November 21-23, 2008. Proceedings)

Broadcasting: Wie verbreite ich schnell Informationen? - Scheideler, Christian (Taschenbuch der Algorithmen)

INFORMATIK 2008, Beherrschbare Systeme - dank Informatik, Band 1, Beiträge der 38. Jahrestagung der Gesellschaft für Informatik e.V. (GI), 8. - 13. September, in München, Deutschland